Evidence for Neoproterozoic continental arc magmatism in the Santa Quitéria Batholith of Ceará State, NW Borborema Province, NE Brazil: Implications for the assembly of West Gondwana - Fetter, Allen H. [UNESP]; Saraiva dos Santos, Ticiano J.; Van Schmus, William R.; Hackspacher, Peter C. [UNESP]; de Brito Neves, Benjamin Bley; Arthaud, Michel H.; Nogueira Neto, José A.; Wernick, Eberhard [UNESP] (Elsevier, 2003)
Recent field investigations and geochronological studies of Neoproterozoic rocks in the northwestern part of the Borborema Province, Ceará State, NE Brazil provide important clues pertaining to the nature of convergence between the Borborema Province and the West African-São Luis craton during the assembly of West Gondwana. U-Pb zircon data indicate that the earliest evidence of convergent magmatism along the northwest margin of the Borborema Province occurred around 777 Ma, and was followed by the development of a large continental arc batholith (Santa Quitéria batholith) between ca. 665 and 591 Ma within the central part of Ceará State. These findings, along with supporting geophysical data, suggest that convergence between the Borborema Province and the West African-São Luis craton involved closure of an oceanic realm with subduction polarity to the southeast beneath the northwestern part of the province. Consequently, it seems likely that the Pharusian Ocean was continuous from the Hoggar Province in West Africa into South America during the late Neoproterozoic and additional data suggests that it may have even been connected with the Goianides Ocean of the Brasília Belt farther to the southwest.
Keywords: Borborema Province; Ceará State; Geochronology; Santa Quitéria Batholith; West Gondwana; batholith; continental arc; convergence; geochronology; Gondwana; magmatism; Proterozoic; tectonic evolution; Brazil